A Theoretical Model of On-the-Job Training with Imperfect Competition. - Stevens, M (1994)
Training for skills that are transferable to other firms, but for which the external labor market is imperfectly competitive, cannot be analyzed using the traditional tools of general and specific training. It is known that firms (as well as workers) have an incentive to invest in such training but that there is an externality problem that may lead to underinvestment. Using a formal model, it is shown that the problem is most severe at 'intermediate' levels of labor-market competition. The effects are that too few workers are trained and there is overinvestment in purely specific training.